Factors influencing perception and knowledge of exclusive breast feeding practices among nursing mothers in rural area of Thane district of Mumbai - Srivastava, Abhay S.; Gawande, Kanchan B. (International Journal Of Community Medicine And Public Health, 2018)
Background: Exclusive breastfeeding (EBF) is recommended as the best feeding alternative for infants up to six months and has a protective effect against mortality and morbidity. Exclusive breastfeeding (EBF) is one of the optimal infant and young child feeding practices. Globally, <40% of infants under 6 months of age are exclusively breastfed. According to NFHS4 data (2015 -16) the prevalence of EBF in the rural area of Maharashtra was 60.6% which was far less than the 100% recommended by the United Nation Children Emergency Fund. Objective: Study was conducted to find the mothers knowledge and perception on breast feeding practices and other factors which influences breast feeding practices in the study area. Methods: A cross sectional descriptive study was employed. From the population of 8000, by applying convenient sampling technique, 152mothers attending the Primary Health Centre with children less than 2 years of age were enrolled after taking informed consent. Result: The prevalence of exclusive breast feeding was 63.15%. There was a significant association between socio‑demographic characteristics of mothers such as occupation (p<0.05), type of family (p<0.05) and the practice of exclusive breastfeeding. Conclusion: As it was found that exclusive breast feeding was practiced well by mothers who were housewives which shows that employment was the major obstacles for breast feeding.